Efficacy of Ciprofloxacin-Releasing Bioabsorbable Osteoconductive Bone Defect Filler for Treatment of Experimental Osteomyelitis Due to Staphylococcus aureus - Koort, Jyri K. (American Society for Microbiology, 2005)
The concept of local antibiotic delivery via biodegradable bone defect fillers with multifunctional properties for the treatment of bone infections is highly appealing. Fillers can be used to obliterate surgical dead space and to provide targeted local bactericidal concentrations in tissue for extended periods. Eventually, the osteoconductive component of the filler could guide the healing of the bone defect. The present experimental study was carried out to test this concept in a localized Staphylococcus aureus osteomyelitis model in the rabbit (n = 31). A metaphyseal defect of the tibia was filled with a block of bone cement, followed by insertion of a bacterial inoculum. After removal of the bone cement and surgical debridement at 2 weeks, the defect was filled with a ciprofloxacin-containing (7.6% ± 0.1%, by weight) composite (treated-infection group) or with a composite without antibiotic (sham-treated group). Both a positive control group (untreated-infection group) and a negative control group were also produced. The treatment response, monitored by positron emission tomography (PET) with fluorine-18-labeled fluorodeoxyglucose ([(18)F]FDG) at 3 and 6 weeks, showed rapidly decreasing amounts of [(18)F]FDG uptake in the treated-infection group (P = 0.001 compared with the results for the untreated-infection group at 6 weeks). The bacteriological analysis confirmed the eradication of the bone pathogen in the treated-infection group. However, three animals had culture-positive soft tissue infections. All animals in the sham-treated and untreated-infection groups had culture-positive bone infections with typical radiographic changes of osteomyelitis. Histomorphometry, peripheral quantitative computed tomography, and backscattered electron imaging of scanning electron microscopy images verified the osteoconductive properties of the bioactive glass microspheres within the composite. The median bone ciprofloxacin concentrations were 1.2 and 2.1 μg/g at two anatomic locations of the tibia. This is the first report to show the value of [(18)F]FDG PET for quantitative monitoring of the treatment response in bone infections. The collaborative results of bacteriologic and [(18)F-FDG] PET studies showed that use of the multifunctional composite was successful for eradication of the S. aureus pathogen from bone.